Workshop Publish or Perish - Aini Norhidayah, Mohamed (2023)
A workshop titled "Publish or Perish" was successfully held on March 16th, 2023. The speaker was Assoc. Prof. Dr. Ahmad Salihin bin Muhamad, an experienced academician in publishing research journals from Faculty of Industrial Sciences and Technology, and was attended by 40 postgraduate students.